Effect of post-polymerization with autoclaving treatment on monomer elution and mechanical properties of 3D-printing acrylic resin for splint fabrication - Sakarin Tangpothitham (2022)
Objectives: To evaluate the effect of post-treatment autoclaving on monomer elution and mechanical properties of three-dimensionally (3D) printed resin for splint fabrication. Methods: Photopolymer resin specimens (Dental LT Clear) were 3D-printed and processed according to the manufacturer's instructions. The specimens were randomly divided to different post-treatment protocols: water storage, autoclaving at different temperatures (121 °C or 132 °C), times (4 or 30 min) and no treatment as a control. The elution of UDMA, HEMA, and EGDMA monomers was determined using high-performance liquid chromatography (HPLC) by immersing the specimens in 75% ethanol for 72 h. The flexural modulus, surface microhardness and linear dimensional changes were measured. The monomer elution and flexural modulus were statistically analyzed using Welch's ANOVA followed by Dunnett's T3 tests, while the surface microhardness and dimensional changes were analyzed using one-way ANOVA followed by Bonferroni tests (α = 0.05). Results: The overall monomer elution concentrations were significantly highest for the control group and lowest for specimens treated in an autoclave at 132 °C for 4 min. The flexural modulus was not significantly different between all groups. The surface microhardness was significantly higher for all autoclaved groups than the control and water storage groups. The linear expansion was significantly higher after post-treatment autoclaving in contrast to water storage. Significance/conclusions: Post-polymerization autoclave treatment of the 3D-printed resin reduced monomer elution and improved surface microhardness without deteriorating the flexural modulus. Post-treatment with an autoclave at 132 °C for 4 min can be recommended for 3D-printed resin for splint fabrication.